2005
DOI: 10.1093/brain/awh713
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging of brain reorganization in motor areas of the contralesional hemisphere of well recovered patients after capsular stroke

Abstract: Clinical recovery after stroke can be significant and has been attributed to plastic reorganization and recruitment of novel areas previously not engaged in a given task. As equivocal results have been reported in studies using single imaging or electrophysiological methods, here we applied an integrative multimodal approach to a group of well-recovered chronic stroke patients (n = 11; aged 50-81 years) with left capsular lesions. Focal activation during recovered hand movements was assessed with EEG spectral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
291
1
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(337 citation statements)
references
References 123 publications
39
291
1
6
Order By: Relevance
“…From these studies, it seems that inhibiting the contralesional M1 is one way to improve function of the lesional M1. Yet, we know from our results and others (Gerloff et al, 2006) that the uncrossed corticospinal tract from the contralesional M1 is not directly involved in the return of motor activity in the recovered hand, because MEPs were not recorded in the ipsilateral (recovered) FDI while stimulating the contralesional hemisphere using TMS, even at maximal stimulator output (Foltys et al, 2003) (despite contralesional M1 activation during wrist and index finger tasks in patients).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…From these studies, it seems that inhibiting the contralesional M1 is one way to improve function of the lesional M1. Yet, we know from our results and others (Gerloff et al, 2006) that the uncrossed corticospinal tract from the contralesional M1 is not directly involved in the return of motor activity in the recovered hand, because MEPs were not recorded in the ipsilateral (recovered) FDI while stimulating the contralesional hemisphere using TMS, even at maximal stimulator output (Foltys et al, 2003) (despite contralesional M1 activation during wrist and index finger tasks in patients).…”
Section: Discussionmentioning
confidence: 53%
“…An alternative explanation is that contralesional M1 activation arises from top-down activation from higher order areas, and is an epiphenomenon not contributing to recovery. Gerloff et al (2006) using EEG coherence analysis recently showed that after stroke, corticocortical connections were reduced in the stroke-affected hemisphere but increased in the contralesional hemisphere, suggesting a shift of functional connectivity towards the contralesional side. Short and long-range connectivity from within (Fridman et al, 2004) and across the hemisphere (Johansen-Berg et al, 2002b) is known to affect the excitability of the cortex and hence contribute to motor recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Beta rhythms during MI have been correlated to sensorimotor processes in healthy subjects (McFarland et al, 2000) and stroke patients (Gerloff et al, 2006). In the latter, the relative asymmetry between ipsilesional and contralesional hemispheres during contralateral MI and its relationship with functional motor impairment remain debated (Graziadio et al, 2012;Shahid et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, all measures of FC are sensitive to noise and the alpha band tends to have a greater signal-to-noise ratio, especially compared to faster rhythms. Furthermore, our analyses were restricted to the resting-state whereas other EEG frequencies may be more implicated during tasks (Gerloff et al, 2006).…”
Section: The Role Of Alpha Oscillation Synchrony After Strokementioning
confidence: 99%